i-cPEdS as an Alternative learning platform for pediatricians in Southern Tagalog - Casubha, Crisphin L.
As a continuum of learning from basic medical education and postgraduate medical education, the continuing professional development (CPD) is needed to answer for the social accountability of a medical (pediatric) practitioner. In order to be updated with medical trends, the pediatrician must apply self-directed learning. A form of self-directed learning is using an online continuing professional development site, called i-cPEdS. This site was created for member pediatricians of the Philippine Pediatric Society's Southern Tagalog Chapter (PPSSTC). With the chapter's members spread out the over vast geographic locations, as an online CPD should be in place. Objectives: Determine the effectiveness in terms of experience of i-cPEdS as an alternative learning platform for member pediatricians of the Southern Tagalog Region. Specifically, the study aimed to describe i-cPEdS as an alternative learning platform in terms of learning, learning experiences, and consistency of the design of the session. This quantitative descriptive cross-sectional survey study used 340 member-pediatricians of the chapter as the sample population. A month's data collection was used in this study. The respondents answered the pretest that was composed of 10 multiple-choice questions prior to viewing the recorded video of the CPD topic of the month. A posttest followed the video. After completion of the posttest, respondents were directed to the last section of the questionnaire wherein questions pertaining to the experience were asked. Measures of central tendency and paired T-test were used to analyze the data. Member pediatricians of PPSSTC had a significant increase in posttest scores from pretest. Participants' responses on their learning experiences responses leaned toward favorable results that may signify the effectiveness of i-cPEdS as a CPD delivery platform. The design of the session in i-cPEdS was also found as appropriate in achieving intended learning outcomes and consistent with the outcome-based education framework. Conclusion: i-cPEdS is an effective alternative learning platform for pediatricians in the Southern Tagalog Region. Pediatricians in the Southern Tagalog Region who used this alternative learning platform are attuned with the use of information technology for delivering effective CPD activities. The design elements of the particular online session of i-cPEdS used in this research was consistent in terms of the objectives, content, strategy and assessment.